Abreviasi dalam Bahasa Inggris - Isa, Arie Andrasyah (UI Scholars Hub, 2006)
This study is concerned with a productive word-form process in the morphological level, such as abbreviation. Through the process of the word form, I intend to find out how to make new words in using the abbreviation in English. Besides, I intend to review the concept of abbreviation. The aim of this study is also to observe how the abbreviation can form new words. The data employed in this study are from newspaper Jakarta Post and Kompas, and examples provided by the related linguists. With the data exemplified by the linguists and based on their discussion on abbreviation, I think there are some mistakes on information and definitions provided by them about the abbreviation. Hence, I try to present and find out new information about the abbreviation and its types morphologically. As the result of this study, there are 16 types of abbreviation. They are (1) acronyms, (2) part acronyms, (3) amalgam, (4) blends, (5) loan blends, (6) element blends, (7) part-whole blends, (8) lexical blends, (9) separated blends, (10) contraction, (11) letter symbol, (12) clippings, (13) alphabetism, (14) sycronyms, (15) acronym coinages, and (16) analogical forms.